2019
DOI: 10.3390/s19092065
|View full text |Cite
|
Sign up to set email alerts
|

Robust Smartphone Assisted Biosensing Based on Asymmetric Nanofluidic Grating Interferometry

Abstract: Point-of-care systems enable fast therapy decisions on site without the need of any healthcare infrastructure. In addition to the sensitive detection, stable measurement by inexperienced persons outside of laboratory facilities is indispensable. A particular challenge in field applications is to reduce interference from environmental factors, such as temperature, to acceptable levels without sacrificing simplicity. Here, we present a smartphone-based point-of-care sensor. The method uses an optofluidic grating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With an improved measurement setup, the presented detection principle could prove useful in future point-of-care devices for antimicrobial susceptibility testing (AST) where no overnight culture and labeling of the bacteria is possible. It has been shown that a similar optical setup can be realized for protein detection based on a smartphone [ 25 ]. In future studies, we plan to investigate if a dependence of the antibiotic concentration can be correlated with the measuring signal of the setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an improved measurement setup, the presented detection principle could prove useful in future point-of-care devices for antimicrobial susceptibility testing (AST) where no overnight culture and labeling of the bacteria is possible. It has been shown that a similar optical setup can be realized for protein detection based on a smartphone [ 25 ]. In future studies, we plan to investigate if a dependence of the antibiotic concentration can be correlated with the measuring signal of the setup.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a hydrodynamic bacterial cell-trapping principle which has been recently been reported [ 24 ] is now implemented in the form of a regular nanogap array to allow readout with an interferometric method. Here, we present an optofluidic chip which can immobilize bacteria in an optical asymmetric grating to measure the proliferation of bacteria with high sensitivity by interferometry based on optofluidic concepts that, in the past, had been developed to measure surface bound molecules [ 25 , 26 ]. This study describes the fabrication and characterization of the optofluidic nanosystem and shows the applicability of this approach in future ASTs.…”
Section: Introductionmentioning
confidence: 99%
“…Purr et al prepared a device with asymmetric interdigitating arrangement of detection and reference nanochannels to directly calculate the refractive index [ 23 ]. This nanofluidic device could also be integrated into a smartphone-based biosensing system [ 24 ].…”
Section: Optical Detectionmentioning
confidence: 99%